A longer way in: Tryouts as alternative hiring arrangements in organizations. (2019) - Sterling, Adina; Merluzzi, Jennifer
Abstract: In this article we introduce and propose a research agenda on tryouts, a hiring arrangement in which individuals spend time in organizations performing job-related work prior to the chance to become regular, full-time employees. We define tryouts as a construct and discuss how tryouts differ from traditional, direct hiring. We provide a typology of alternative hiring arrangements that serve as tryouts and evidence for their utilization. We theorize that tryouts stem from changes in the nature of work, organizations, and labor markets in the 21st century. For labor market researchers, we raise questions about not only the consequences of tryouts—such as who is hired, what kinds of jobs they lead to for workers, and the social and economic awards attached to such jobs—but also about the motivations of individuals who engage in tryouts, how these motivations (and the consequences of tryouts) differ across demographic groups, and how tryouts may create multi-tiered hiring systems. For organizational scholars, we suggest that tryouts update theoretical conceptualizations of hiring, and lead organizational behaviors to commence during hiring that demand further attention. While worthy of study in their own right, we also discuss reasons that tryouts offer an "ontological laboratory" for assessing theories on organizations, labor markets, and the origins and remediation of workplace inequality.